Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa - Intan Tri Handayani; Marlina Eliyanti Simbolon; Isnaini Wulandari (KOLONI, 2023)
This research is motivated by problems by learning mathematics in the second grade students of SD Negeri 1 winduhaji, in which learning outcomes is still low. The purpose of this research was to find out the differences and improvements in student learning outcomes between classes using the problem-based learning model and conventional methods (lectures). The method used in this research was a quantitative research method with a quasi-experimental research type and the from of quasi-experimental design used was non-equivalent control group design. The instrument in this study was using multiple choice tests and limited descriptions. For subjects of this research were all of the second grade students of SD Negeri 1 Winduhaji, where class A as the control class and class B as the exsperimental class. It can be concluded that there are differences and improvements between classes using the problem-based learning model and conventional methods (lectures) on student learning outcomes, but not significant in the mathematics subject matter of standard length units in class II of SD Negeri 1 Winduhaji. The class received treatment using the problem based learning model was class II B.  Keywords: Learning Outcomes, Mathematics, Problem Based Learning